Cat behaviour in the secure base test: Comparison between owned and shelter animals - Takeda, Cinthia Sayuri Yoshizawa; Luchesi, Suzana Helena; Martins, Fernanda Peixoto; Trindade, Pedro Henrique Esteves [UNESP]; Damasceno, Alexsandro Antonio Portilho; de Souza Gomes, Igor; dos Santos, Rayane Gonçalves; de Souza Monteiro, Juliana Roberta; Otta, Emma (Elsevier, 2024)
The aim of the present study was to compare affiliative behaviours of owned and shelter cats directed to human in a novel environment after a brief temporary absence of the person. A sample of 20 owned and 20 shelter animals were individually tested in a Secure Base Test, with three 2-min episodes: 1) cat accompanied by a person who sits on the floor inside a circle, 2) the person leaves and the animal is left alone, 3) the person returns, and sits inside the circle again. Three categories were used for coding videotapes of experimental sessions: (1) inside circle, (2) allo-rubbing and (3) tail up. Shelter animals showed more proximity maintenance and affiliative signs with a person than owned animals. Our findings suggested similarities between the secure base effect in cats and in human children: cats seek proximity and maintain contact with a person, displaying affiliative signs to the person, especially after being left alone frightened by an unfamiliar environment.
Keywords: Attachment; Cat; Interspecific relationship; Secure Base Test